In vitro susceptibility testing of dermatophytes with their fragmented mycelia as inoculum - Czaika, V. A.; Schmalreck, A.F. (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
377 clinical isolates and seven dermatophyte culture collection strains were tested in vitro by microdilution against a panel of 18 antifungal agents. A newly introduced method for rapid and reliable inoculum preparation for moulds using the fragmented mycelia of freshly grown isolates as inoculum was firstly applied to dermatophytes. The performance of the method was tested with two different culture media which are recommended by different standardized testing methods for moulds. The standardized fragmented mycelia provided both, countable single colonies (viable units) on solid culture media and distinct readable endpoints (minimum inhibitory concentrations) in the microdilution wells for all tested topical and systemic drugs, including the echinocandins. As with moulds, and as shown by the culture collection strains, reproducible minimum inhibitory concentrations were obtained with an essential agreement (± 1 log2-dilution) of 97% to 100%, by a significant reduction of the overall testing time. As exemplarily shown for the microdilution technique, this inoculum method should also provide a solid basis for improved agar-based susceptibility testing methods such as disc-, tablet-, or strip-tests.